Traumatic Posterior Urethral Strictures in Children and Adolescents - Podesta, Miguel; Podesta, Miguel (Frontiers in Pediatrics, 2019)
Background: Management of partial or complete traumatic urethral disruptions of the posterior urethra in children and adolescents, secondary to pelvic fracture poses a challenge. Controversy exists as to the correct acute treatment of posterior urethral injuries and delayed management of PFPUDDs. We reviewed the urological literature related to the treatment of traumatic posterior urethral injuries and delayed repair of these distraction defects in children and adolescents. Material and Methods: There are few long-term outcomes studies of patients who underwent PFPUDDs repairs in childhood; most reports included few cases with short follow up. We excluded studies in which the cohort of patients was heterogeneous in terms of stricture disease, etiology and location. Results: Primary cystostomy and delayed urethroplasty is the traditional management for PFPUIs. Immediate repair is rarely possible to perform. Realignment of posterior urethral rupture in children is indicated in special situations: (a) concomitant bladder neck tears, (b) associated rectal lacerations, (c) long disruptions of the urethral ends. Before delayed reconstruction ascending urethrography and micturating cystourethrogram along with retrograde and antegrade urethroscopy define site and length of the urethral gap. However, the most accurate evaluation of the characteristics of the distraction defect is made when surgical exposure reveals the complexity of the ruptured urethra. Partial ruptures may be managed with urethral stenting or suprapubic cystostomy, which may result in a patent urethra or a short stricture treated by optical urethrotomy. The gold standard treatment for PFPUDDs in children is deferred excision of pelvic fibrosis and bulbo-prostatic tension-free anastomosis, provided a healthy anterior urethra is present. Timing of delayed repair is at 3 to 4 months after trauma. Some urologists prefer either the perineal access or the transpubic approach to restore urethral continuity in children with PFPUDDs. Substitution urethroplasties are used in children with PFPUDDs, when anastomotic repair can't be achieved due to severe damage of the bulbar urethra. Conclusion: As evidenced in this review the progressive perineo-abdominal partial transpubic anastomotic repair has advantages over the isolated perineal anastomotic approach in patients with “complex” PFPUDD. This approach provides wider exposure and facilitates reconstruction of long or complicated posterior urethral distraction defects